2006
DOI: 10.1111/j.1749-4486.2006.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment after non‐laser endonasal dacryocystorhinostomy

Abstract: Successful non-laser endonasal dacryocystorhinostomy does confer significant quality of life improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
2
30
0
6
Order By: Relevance
“…Although we admit that there could be a gratitude bias with a face-to-face interview, there are several published studies that use the GBI questionnaire with a face-to-face interview, showing reliable results 15 16. Ho et al 15 administered the GBI questionnaire during one of their clinic visits and reported that the total GBI scores were +34 for the successful DCR group and −19 for the failed DCR group. Interestingly, the authors showed a reasonable correlation between GBI score and subjective symptoms at a minimum of 9-month follow-up with a face-to-face interview.…”
Section: Discussionmentioning
confidence: 92%
“…Although we admit that there could be a gratitude bias with a face-to-face interview, there are several published studies that use the GBI questionnaire with a face-to-face interview, showing reliable results 15 16. Ho et al 15 administered the GBI questionnaire during one of their clinic visits and reported that the total GBI scores were +34 for the successful DCR group and −19 for the failed DCR group. Interestingly, the authors showed a reasonable correlation between GBI score and subjective symptoms at a minimum of 9-month follow-up with a face-to-face interview.…”
Section: Discussionmentioning
confidence: 92%
“…It was originally validated for use in otorhinolaryngological patients and although its use in ptosis surgery has been reported, [30][31][32] validity data in the currently studied population is limited. Despite the risk of response bias inherent in its design, the GBI is a generic and translatable instrument that can measure both positive and negative impact (scored from +100 to − 100) across a range of procedures; 32,33 it has been shown to correlate with both markers of surgical success [34][35][36] and quality of life. 37 The positive score of +21.8 is comparable with previous reports for ptosis surgery, with mean total scores consistently between +21 and +25, adding some support for its reliability in this population.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Ho et al concluded that nonlaser EN-DCR confers a significant quality of life improvement. 10 Bakri et al compared the benefit of laser-assisted EN-DCR and EX-DCR. They found no significant difference in GBI scoring between the two groups.…”
Section: Current Eye Researchmentioning
confidence: 98%
“…It has also been recommended for the evaluation of outcomes after DCR. 9,10 The questionnaire consists of 18 questions. The responses to each question are chosen based on a 5-point scale ranging from a large deterioration in health status to a large improvement in health status.…”
Section: Postoperative Outcome Assessmentmentioning
confidence: 99%